New Orleans Memories : One Writer's City - Kolb, Carolyn, 1942- (Book collections on Project MUSE., 2013)
The author provides a delightful and detailed look into the heart of her city, New Orleans. She is a former Times-Picayune reporter and columnist for New Orleans Magazine, where versions of these essays appeared as "Chronicles of Recent History." She takes her readers, both those who live in New Orleans and those who love it as visitors, on a virtual tour of her favorite people and places. Divided into sections on food, Mardi Gras, literature, and music, these short essays can be read in one gulp or devoured slowly over time. Either way, the reader will find a welcome companion and guide in this book.